#TITLE_ALTERNATIVE# - GUSTI AGUNG AYU MAS OKA (NIM : 23607027); Pembimbing : Dr. Hisar M. Pasaribu , I
The advent of new airlines operating with the low cost model, result in increasing of flight movement, which has been predicted to already close to the runway capacity at Soekarno-Hatta Airport. Therefore, there is a need to calculate the maximum runway capacity at Soekarno-Hatta Airport and analyze the efforts to enhance the capacity. The purpose of this research are to calculate the ultimate capacity of runway, to investigate the efforts to enhance the capacity and to analyze the efforts which has more profound effect. Two methods are used to calculate the ultimate capacity of runway, i.e. the mathematical formulation and the FAA’s method. The result of the hourly runway capacity with the mathematical calculation is 42 operations for arrival only, 110 operations for departure only and 64 operations for mix. Whereas using the FAA’s method , it gives 76 operations for VFR condition and 71 operations for IFR condition. To enhance the runway capacity, some strategies are researched, such as reduction of separation to meet criteria set by FAA’s rule, addition of the exit taxiway, addition of the runway according to master plan of Soekarno-Hatta Airport and changing the runway utilization strategies. Out of the four strategies, the most eficient solution is changing the runway utilization strategies (with capacity increase of 35,9 %) and reduction in separation (with capacity increase of 34,4 %). However, the addition of runway has the highest capacity increase, that is 53,9 %. The existing maximum operation per hour is 64 operations. That means it has already reached the maximum runway capacity at Soekarno-Hatta Airport. Therefore, the Soekarno-Hatta Airport authority has to enhance the runway capacity to anticipate the demand increase in the future.